Non-target molecular network and putative genes of flavonoid biosynthesis in Erythrina velutina Willd., a Brazilian semiarid native woody plant - Chacon, Daisy Sotero; Santos, Marlon Dias Mariano; Bonilauri, Bernardo; Vilasboa, Johnatan; da Costa, Cibele Tesser; da Silva, Ivanice Bezerra; Torres, Taffarel de Melo; de Araújo, Thiago Ferreira; Roque, Alan de Araújo; Pilon, Alan Cesar; Selegatto, Denise Medeiros; Freire, Rafael Teixeira; et al. (Frontiers in Plant Science, 2022)
Erythrina velutina is widely used in traditional medicine with anti-inflammatory and central nervous system modulating activities. This species is a rich source of specialized metabolites, mostly alkaloids and flavonoids. To date, genomic information and biosynthesis and regulation of flavonoids remain unknown. As a step to address this knowledge gap, leaves and seeds of plants growing in their natural habitat had their metabolic and proteomic profiles analyzed and integrated with transcriptome data. As a result, 96 metabolites (including 43 flavonoids) were annotated. Transcripts of the flavonoid pathway totaled 27, of which EvCHI, EvCHR, EvCHS, EvCYP75A and EvCYP75B1 were identified as putative main targets for modulating the accumulation of these metabolites. The highest correspondence of mRNA vs protein was observed in the differentially expressed transcripts. In addition, 394 candidate transcripts encoding for transcription factors distributed among the bHLH, ERF, and MYB families were annotated. Expression patterns of transcripts involved in flavonoid biosynthesis and those involved in responses to biotic and abiotic stresses are discussed in detail. These findings will contribute to the establishment of a solid base for the understanding of molecular and metabolic responses in this medicinally important Brazilian semiarid species. Moreover, the identification of key regulatory targets for future studies aiming at bioactive metabolite production will be facilitated.